Cognitive Training for Very High Risk Incarcerated Adolescent Males - Rowlands, Abby; Fisher, Melissa; Mishra, Jyoti; Nahum, Mor; Brandrett, Benjamin; Reinke, Michael; Caldwell, Michael; Kiehl, Kent A.; Vinogradov, Sophia (Frontiers in Psychiatry, 2020)
Objective. Persistent violent and antisocial behavior, as manifested in Conduct Disorder (CD) traits, are associated with a range of cognitive deficits. Individuals with more severe cognitive deficits are more likely to commit violent crimes. Currently, no treatments target improving cognition in high-risk CD youth. This pilot study tests the feasibility and efficacy of delivering intensive tablet-based cognitive training (CT) to adolescent males incarcerated in a youth maximum-security prison. Methods. Participants were fourteen adolescent males, diagnosed with CD. All participants completed up to 30 hours of unsupervised, intensive, adaptive CT exercises that targeted multiple neurocognitive domains, as well as a battery of standardized neurocognitive measures and computerized assessments at baseline and post-training. Conclusions & Implications for Practice. At baseline, participants exhibited significant impairments on neurocognitive measures, relative to age-matched healthy controls. Twelve participants completed training and showed evidence of target engagement, as indexed by improvement in cognitive processing speed. Significant gains were observed in measures of global cognition, with additional gains in cognitive flexibility at trend level significance. Improvements in these measures were positively related to total training time. In summary, both assessments and intervention appear to be feasible, tolerable and acceptable in incarcerated youth. Intensive CT shows preliminary efficacy in improving neurocognitive performance in key domains, with large effect sizes, and significant performance improvement associations with the time in training.